Effectiveness of a single-tuft toothbrush for control of newly formed dental biofilm - Iohana Hasegawa; Camila Veríssimo; Victor Angelo Montalli; Marcelo Sperandio; Daiane Cristina Peruzzo (Universidade Estadual de Campinas, 2017)
Aim: To compare the effectiveness of a single-tuft toothbrush (STB) with conventional toothbrushes (CT) to control dental biofilm neoformation in the dentogingival area. Methods: For this cross-sectional  prospective blind study, 20 periodontally healthy subjects were selected and randomly divided into 4 groups: STB; CT; CHX - chlorhexidine mouthwash (positive control) and PS - placebo mouthwash (negative control). The subjects were instructed to use only the assigned care method for 72 h with a 7-day washout period between experiments. The evaluated parameters were visible and disclosed plaque indices (PI and DPI), gingival bleeding index (GBI) at baseline (T-0) and at the end of each experimental period (T-72). Results: Data analysis demonstrated that at T-0 no difference was observed for any of the parameters (p>0.05); after 72 h, CT, STB and CHX showed equivalente effectiveness at controlling biofilm. When the PI data were analyzed, between T-0 and T-72, STB was similar to CT and CHX (p<0.05), whereas for DPI, STB was significantly superior to the other methods. Except for PS, all methods yielded similar results for GBI (p<0.05). Conclusions: The tested STB was effective at controlling short-term dental biofilm neoformation on the dentogingival area.